KETIDAKSANTUNAN BERBAHASA PADA MEDIA JEJARING SOSIAL FACEBOOK - Ahmad Maulidi (Multilingual, 2018)
This research is aim at explaining the use of language in social media including language impoliteness occurring in social media Facebook. This research is a qualitative research which uses two research approaches which are theoretical and methodological approaches. The data in this research is in the form of written data which is the Facebook users’ status updates that are considered violating politeness principles. The data obtained uses monitoring method by noting down every single discourse from Facebook media. The data gathered was analyzed by using normative method. Based on the result of the research, it can be presented that the use of language in social media Facebook embodies impoliteness. Moreover, the form of impoliteness in Facebook media materializes in discourse data embodying generosity impoliteness, humility impoliteness, acceptance impoliteness, sympathy impoliteness, and incompability impoliteness.